O ensino de análise combinatória com aulas expositivas e fichas de aula em uma escola de ensino médio do interior paulista - Silva, Rodrigo do Carmo (2012)
The following paper is a description of a research performed with second year of high school students, in a school in the inland of the state of São Paulo, over the topic of Combinatorial Analysis. Such topic is normally neglected in this teaching level. According to the National Teaching Parameters (Parâmetros Curriculares Nacionais PCN), the topic of Combinatorial Analysis is a theme with its place in the normal contents of the second year of high school, being so, the intervention was performed with students of this level. The intervention entails two Diagnoses Files (one applied in the beginning of the research, and the other in the end, serving as a comparison tool) and three Classroom Files, which take into consideration all the Combinatorial Analysis to be developed in High School. Each Diagnosis File has 5 exercises about counting, and each Classroom File has a summary of the theory developed with the participation of the teacher and the students in the form of theoretical and practical classes, and some exercises for the application of the theory developed in the Classroom File. Analysis, comments and comparisons collected by the teacher in the application of the classroom files are described in this paper. The final product of this Master degree thesis is available in the web site of Programa de Pós Graduação em Ensino de Ciências Exatas PPGECE (Postgraduate program of exact sciences teaching): www.ppgece.ufscar.br